Bovine hydatid disease: Contrasting of macroscopic and microscopic diagnosis (Veterinary Science, 2017)
The causative agent of hydatid disease in our country is the Echinococcus granulosus. This parasite takes canids as definitive hosts and ruminants, pigs, wild species and human as intermediate hosts. All organs with suspicious lesions of hydatid disease are seized and removed in slaughterhouses. This provides important data to understand the disease, its prevalence and distribution, to evaluate the control and eradication plans and value new diagnostic techniques and treatment. There are two critical points for the diagnosis: those organs in which metacestodes are present but not macroscopically visible and those who are seized by submitting hydatid - like lesions but with different etiology. This last aspect was studied considering as hypothesis the lack ofrelationship between macroscopic and microscopic diagnoses. The organs with macroscopic lesions were sent to the laboratory. Selected samples were studied, were characterized morphologically and topographically and were processed by routine techniques of paraffin embedding and staining with hematoxylin and eosin. The positive histopathological diagnosis was based on observation of the morphology of a total of 105 samples diagnosed as hydatid disease, 15 were negative by histopathological diagnosis.
Keywords: Bovine hydatid disease; Hydatid disease; Slaughter inspection; Macroscopic diagnosis